Overwiew on selective breeding and genetic improvement in bivalve shellfish - Boudry, Pierre (IVth EFARO Workshop Genetics tools for fisheries and aquaculture development, 2004)
Dr. Boudry focussed his talk on oysters, which are the most important bivalve species produced world wide (more than 4 million tons). One of the main characteristic of bivalve aquaculture is that most of the juveniles ("seed or "spat") are collected from natural recruitment (e.g. 100% of the European mussel production). Hatchery propagation is used in the case of introduced species (e.g. Crassostrea gigas in USA) or limited natural recruitment. The most significant genetic improvement for the production of Pacific oyster (C. gigas) to date has been obtained through the breeding of triploids, especially since the development of tetraploids. Triploidy lead to highly reduced gametogenesis and, as a result better growth and survival. Many quantitative genetics studies suggest that significant gains, for disease resistance or for other traits of aquacultural interest, could be obtained using selective breeding. However, the limited extent of hatchery-propagation (versus natural recruitment) and/or various technical difficulties and biological characteristics of the species have slowed the development of selective breeding programs. Recently, in the U.S.A., Australia and New Zealand, family-based selective breeding programs have been initiated to improve growth and yield. In Europe, where both natural and hatchery-propagated spat are farmed, no large scale selective breeding programs have yet been initiated. However, special attention has been paid to "summer mortalities", for which the causal factors are still unclear. Studies have shown that family-based selective breeding can improve spat survival, with no impact on growth. However, a genetic trade-off between survival and reproductive allocation was shown in adults, but was influenced by environmental variation. This might explain how additive genetic variance for fitness-related traits is maintained in wild populations. Practical difficulties in breeding large numbers of families are a major constraint for family-based selective breeding in oysters. Genetic variability exists for several larval traits, which increases the imbalance in reproductive success between breeders in hatchery-propagated populations. Multiplexed-microsatellite markers can be efficiently used to trace parentage in mixed-family breeding programs. Finally, new means of introgression of traits of interest from genetically improved diploids to polyploids were presented. They will allow the combination of selective breeding and polyploidization. The main conclusions were that : -Until now, genetic improvement had a relatively limited impact on bivalve production -There are concerns about the interaction between genetically improved stocks and the environment (wild stocks). -Genetically improved bivalves can be developed, assuming hatchery production is feasible and profitable, so that money can be invested in selective breeding programs -Combined selective breeding and polyploidy is complex but promising.